Effects of testosterone replacement therapy withdrawal and re-treatment in hypogonadal elderly men upon obesity, voiding function and prostate safety parameters. (2nd January 2016) - Yassin, Aksam; Nettleship, Joanne E.; Talib, Raidh A.; Almehmadi, Yousef; Doros, Gheorge
Abstract: Whether testosterone replacement therapy (TRT) is a lifelong treatment for men with hypogonadism remains unknown. We investigated long-term TRT and TRT withdrawal on obesity and prostate-related parameters. Two hundred and sixty-two hypogonadal patients (mean age 59.5) received testosterone undecanoate in 12-week intervals for a maximum of 11 years. One hundred and forty-seven men had TRT interrupted for a mean of 16.9 months and resumed thereafter (Group A). The remaining 115 patients were treated continuously (Group B). Prostate volume, prostate-specific antigen (PSA), residual voiding volume, bladder wall thickness, C-reactive protein (CRP), aging male symptoms (AMS), International Index of erectile function – erectile function (IIEF-EF) and International Prostate Symptoms Scores (IPSS) were measured over the study period with anthropometric parameters of obesity, including weight, body mass index (BMI) and waist circumference. Prior to interruption, TRT resulted in improvements in residual voiding volume, bladder wall thickness, CRP, AMS, IIEF-EF, IPSS and obesity parameters while PSA and prostate volume increased. TRT interruption reduced total testosterone to hypogonadal levels in Group A and resulted in worsening of obesity parameters, AMS, IPSS, residual voiding volume and bladder wall thickness, IIEF-EF and PSA while CRP and prostate volume were unchanged until treatment resumed whereby these effects were reversed. TRT interruption results in worsening of symptoms. Hypogonadism may require lifelong TRT.